The cognitive map in humans: spatial navigation and beyond - Epstein, Russell A; Patai, Eva Zita; Julian, Joshua B; Spiers, Hugo J (Nature neuroscience, 2017)
Cognitive maps are internal representations of large-scale navigable spaces. While they have been long studied in rodents, recent work in humans reveals new insights into how cognitive maps are encoded, anchored to environmental landmarks and used to plan routes. Similar neural mechanisms might be used to form ‘maps’ of nonphysical spaces. The 'cognitive map' hypothesis proposes that brain builds a unified representation of the spatial environment to support memory and guide future action. Forty years of electrophysiological research in rodents suggest that cognitive maps are neurally instantiated by place, grid, border and head direction cells in the hippocampal formation and related structures. Here we review recent work that suggests a similar functional organization in the human brain and yields insights into how cognitive maps are used during spatial navigation. Specifically, these studies indicate that (i) the human hippocampus and entorhinal cortex support map-like spatial codes, (ii) posterior brain regions such as parahippocampal and retrosplenial cortices provide critical inputs that allow cognitive maps to be anchored to fixed environmental landmarks, and (iii) hippocampal and entorhinal spatial codes are used in conjunction with frontal lobe mechanisms to plan routes during navigation. We also discuss how these three basic elements of cognitive map based navigation—spatial coding, landmark anchoring and route planning—might be applied to nonspatial domains to provide the building blocks for many core elements of human thought.